Overexpressing p130/E2F4 in mesenchymal stem cells facilitates the repair of injured alveolar epithelial cells in LPS-induced ARDS mice - Xiwen Zhang; Jianxiao Chen; Ming Xue; Yuying Tang; Jingyuan Xu; Ling Liu; Yingzi Huang; Yi Yang; Haibo Qiu; Fengmei Guo (Stem Cell Research & Therapy, 2019)
Abstract Background Low differentiation rates of mesenchymal stem cells (MSCs) limit their therapeutic effects on patients in clinical studies. Our previous study demonstrated that overexpressing p130 or E2F4 affected the multipotential differentiation of MSCs, and the underlying mechanism was attributed to the regulation of the G1 phase. Improving the efficiency of MSC differentiation into epithelial cells is considered to be a new method. Therefore, this study was conducted to evaluate the effects of overexpressing p130 or E2F4 in MSCs on improving re-epithelization in lipopolysaccharide (LPS)-induced ARDS animals. Methods Mouse MSCs (mMSCs) stably transfected with p130 and E2F4 were transplanted intratracheally into LPS-induced ARDS mice. After 7 and 14 days, the mice were sacrificed, and the histopathology of the lungs was assessed by haematoxylin-eosin staining and lung injury scoring. Homing and differentiation of mMSCs were analysed by labelling and tracking mMSCs with NIR815 dye and immunofluorescent staining. Surfactant proteins A and C and occludin in the lungs were assessed by western blot. Permeability was evaluated by analysing the protein concentration of BALF using ELISA. Alveolar fluid clearance was assessed by absorbance measurements of BALF. Lung fibrosis was assessed by Masson’s trichrome staining and Ashcroft scoring. Results The engraftment of mMSCs overexpressing p130 or E2F4 led to attenuated histopathological impairment of the lung tissue, and the lung injury scores of the LPS+mBM-MSC-p130 and LPS+mBM-MSC-E2F4 groups were also decreased (p < 0.05). Overexpression of p130 or E2F4 also increased the retention of mMSCs in the lung (p < 0.05), increased differentiation into type II alveolar epithelial cells (p < 0.05), and improved alveolar epithelial permeability (p < 0.05). Additionally, mMSCs overexpressing p130 or E2F4 inhibited lung fibrosis according to the deposition of collagen and the fibrosis score in the lungs (p < 0.05). Conclusion Overexpressing p130 or E2F4 in mMSCs could further improve the injured structure and function of epithelial cells in the lungs of ARDS mice as a result of improved differentiation of mMSCs into epithelial cells.